The Paradox of Economic Development: Environmental Sustainability and Economic Growth of the Mining Industry in Indonesia - Umar, Umar; Sari, Ema; Umar, Fitriana (SEAN Institute, 2025)
The mining industry in Indonesia plays an important role in national economic development. However, mining activities often result in significant environmental impacts. This creates a paradox between the need for economic growth and environmental sustainability. This study aims to explore the relationship between economic growth generated by the mining sector and its environmental impacts in Indonesia. The study uses qualitative methods with secondary data analysis from government reports, scientific journals and other relevant sources. The results showed a significant conflict of interest between natural resource exploitation and environmental preservation. The study concludes that sustainability-based policies should be integrated in the management of the mining industry to achieve a balance between economic and environmental development.